2008
DOI: 10.1603/0022-0493-101.6.1864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Zoophytophagous Plant Bug <I>Nesidiocoris tenuis</I> (Heteroptera: Miridae) on Tomato Yield

Abstract: Nesidiocoris tenuis Reuter (Heteroptera: Miridae) is one of the most controversial dicyphines because of the injuries it causes to tomato (Solanum esculentum) crops. The aim of this study was to quantify the impact of N. tenuis on fruit yield. Tomato plants were exposed to an average of 0.53 +/- 0.26, 3.4 +/- 1.1, 12.0 +/- 1.4, and 35.2 +/- 7.7 N. tenuis per plant for 3 wk. When fruit were exposed to N. tenuis as flowers, the percentage of aborted fruit was higher in compartments infested with N. tenuis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 3 publications
7
65
0
2
Order By: Relevance
“…When this predator feeds directly from vegetative and reproductive parts of the plant, it produces necrotic rings on stems and leaf petioles, it produces flower abortion, and can also puncture tomato fruits, possibly reducing yields (Sánchez 2008). The intensity of plant feeding by N. tenuis on tomato crops under Mediterranean conditions has been addressed by several authors (Sanchez and Lacasa 2008;Calvo et al 2009;Sanchez 2009;Arnó et al 2010), who concluded that damage caused by this mirid on tomato plants was directly related to the abundance of N. tenuis and inversely related to the interaction between the number of N. tenuis and the number of prey. All these studies were conducted using the sweet potato whitefly Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) as prey.…”
Section: Discussionmentioning
confidence: 99%
“…When this predator feeds directly from vegetative and reproductive parts of the plant, it produces necrotic rings on stems and leaf petioles, it produces flower abortion, and can also puncture tomato fruits, possibly reducing yields (Sánchez 2008). The intensity of plant feeding by N. tenuis on tomato crops under Mediterranean conditions has been addressed by several authors (Sanchez and Lacasa 2008;Calvo et al 2009;Sanchez 2009;Arnó et al 2010), who concluded that damage caused by this mirid on tomato plants was directly related to the abundance of N. tenuis and inversely related to the interaction between the number of N. tenuis and the number of prey. All these studies were conducted using the sweet potato whitefly Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) as prey.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suppression of B. tabaci is a high order objective in most greenhouse tomato production. Nesidiocoris tenuis is known as an effective natural enemy of whitefly (Sánchez & Lacasa, 2008;Calvo et al, 2009) and more recently as potential biological control agent of T. absoluta (Urbaneja et al, 2009). Nesidiocoris tenuis is known as an effective natural enemy of whitefly (Sánchez & Lacasa, 2008;Calvo et al, 2009) and more recently as potential biological control agent of T. absoluta (Urbaneja et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are not the first to describe the efficiency of N. tenuis and M. pygmaeus in managing thrips and whiteflies; this has already been seen in several agricultural crops (Castañé et al, 1996;Riudavets and Castañé, 1998;Blaeser et al, 2004;Bonato et al, 2006;Sánchez and Lacasa, 2008;Calvo et al, 2012b;Malo et al, 2012). However, in the case of sweet pepper, this is the first study that evaluates the effectiveness of both mirids when Calvo et al, 2009aCalvo et al, , 2012avan Lenteren, 2012, van Lenteren et al, 2018.…”
Section: B)mentioning
confidence: 61%
“…Their ability to switch between zoophagy and phytophagy enhanced their establishment and sustained population densities. In turn the population was capable of controlling incipient pest outbreaks early in the season following the initial colonization of the crop by pests or later in the season following a period of pest scarcity (Sánchez and Lacasa, 2008;Castañé et al, 2011). In this group, predatory mirid bugs (Hemiptera: Miridae) such as Nesidiocoris tenuis Reuter ( Fig.1.5) and Macrolophus pygmaeus Rambur ( Fig.1.6) are important predators of several agriculture pests.…”
Section: Zoophytophagous Predatorsmentioning
confidence: 99%
See 1 more Smart Citation